2020
DOI: 10.1136/bmjopen-2019-036183
|View full text |Cite
|
Sign up to set email alerts
|

What influences allied health clinician participation in research in the public hospital setting: a qualitative theory-informed approach

Abstract: ObjectivesUsing theoretical frameworks from implementation science, we aimed to systematically explore the barriers and enablers to research active allied health professionals (AHP) participating and leading research in the hospital setting.DesignA qualitative interview study informed by behaviour change theory.SettingSingle Australian tertiary hospital and health service.ParticipantsWe recruited a convenience sample of 21 AHPs working within a hospital who were seeking to actively participate in/or lead resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 38 publications
(76 reference statements)
3
40
0
Order By: Relevance
“…A lack of financial resources is consistent with the previously published literature [ 31 ], with healthcare organisations placing an increasing emphasis on efficiency of healthcare provision in the context of wider financial constraints and competing pressures [ 32 ]. To ensure resources are allocated to research training and support, AHP research needs to be embedded in the organisations wider vision and strategy [ 33 , 34 ]. Local RCB building strategies need to be designed to maximise efficient use of resources, and clearly support the organisations overall objectives.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of financial resources is consistent with the previously published literature [ 31 ], with healthcare organisations placing an increasing emphasis on efficiency of healthcare provision in the context of wider financial constraints and competing pressures [ 32 ]. To ensure resources are allocated to research training and support, AHP research needs to be embedded in the organisations wider vision and strategy [ 33 , 34 ]. Local RCB building strategies need to be designed to maximise efficient use of resources, and clearly support the organisations overall objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Frontline clinicians must feel capable of adding value to the research process. 16 Last, a recent regional survey of frontline clinician experience with research found that 31.5% of frontline clinicians did not "know how to get started." 17…”
Section: Barriers To Research Engagement For Frontline Cliniciansmentioning
confidence: 99%
“…Key barriers include lack of knowledge and skills, lack of time, competing priorities of organizations, and lack of leadership endorsement (5,6,7). Important enablers include health care professionals' (HCPs) positive beliefs about the consequences of participation in training programs, combined with expert guidance and organizational support (8). HCPs want to provide the best care possible, but many lack the knowledge and skills to move evidence into practice in effective ways.…”
Section: Contributions To the Literaturementioning
confidence: 99%